Communication Strategies to Attract Customers Intentions - Ryan Aditya Syam Putra; Patak, Andi Anto; Korompot, Chairil Anwar (International Journal of Business English and Communication, 2024)
The research examines the communication strategies and factors that influence customer interest in partnering with PT. Pegadaian (CP) Pelita Makassar. The study uses a descriptive, qualitative approach with an interview method to collect data. The research found that PT. Pegadaian (Persero) CP Pelita Makassar uses Word of Mouth, Advertising, and Direct Selling to attract customers and increase revenue by 80%. However, customers' interest in becoming customers at PT. Pegadaian (Persero) CP Pelita Makassar is due to personal needs and the proximity of the outlet to their residence. PT. Pegadaian (Persero) CP Pelita Makassar keeps good relationships with customers through excellent service quality and communication. The research supplies practical and theoretical implications and suggests that PT. Pegadaian (Persero) CP Pelita Makassar should use social media for direct marketing and implement sales promotions to increase customer loyalty.